Highly effective smoothening of 3D-printed metal structures via overpotential electrochemical polishing. Issue 7 (3rd July 2019) - Chang, Shuai; Liu, Aihong; Ong, Chun Yee Aaron; Zhang, Lei; Huang, Xiaolei; Tan, Yong Hao; Zhao, Liping; Li, Liqun; Ding, Jun
ABSTRACT: High roughness of metal structures made by selective laser melting restricted their extensive applications. A strategy of overpotential electrochemical polishing was developed for effectively smoothening three-dimensional (3D)-printed surfaces, particularly for removing sticking particles. Average surface roughness of 0.18 µm was achieved with a small thickness removed of ∼70 µm through a combination of overpotential and conventional electrochemical polishing. Interestingly, micro-lattices polished with this approach nearly doubled the specific compressive plateau stress and energy absorption over as-printed lattices. Moreover, the success with 316L stainless steel, 4130 steel and AlSi10Mg, indicates the potential of this approach for smoothening other 3D-printed metals. GRAPHICAL ABSTRACT: IMPACT STATEMENT: A highly effective technology to smoothen complex and rough 3D-printed metal surfaces is developed using a novel overpotential electrochemical polishing, which can enhance mechanical and functional properties of 3D-printed metals.